Revisiting (dis)fluency: Metacognitive difficulty as a novelty cue that evokes feeling‐of‐interest. Issue 8 (2nd April 2022) - Sung, Billy; Vanman, Eric J.; Hartley, Nicole
Abstract: Contrary to conventional belief and the existing literature, recent research has shown that difficult‐to‐read fonts on marketing communications may evoke perceptual disfluency and enhance consumer evaluation toward unique, complex, or security‐related products. However, no research has examined the psychological mechanism that underlies the positive effects of perceptual disfluency. The current research presents five experiments to address this study gap. Specifically, Studies 1 and 2 provide empirical evidence that perceptual disfluency may lead to perceived novelty and in turn evoke the feeling‐of‐interest, perceived innovativeness, and intention to try a product. Studies 3 and 4 replicate these findings and show that such an indirect effect of perceptual disfluency is mitigated by the presence of salient novelty cues and prior product knowledge, providing further support for the hypothesized disfluency–novelty–interest relationship. Study 5 extended these findings by showing that digital ad banners with disfluent text may enhance click‐throughs in a natural viewing task of a news website. The current findings empirically demonstrate a mechanism that not only underlies the positive effects of perceptual disfluency but also aligns with the fluency–familiarity–liking relationship found in the existing literature.